A berberine hydrochloride-carboxymethyl chitosan hydrogel protects against Staphylococcus aureus infection in a rat mastitis model. (15th February 2022) - Tong, Jinjin; Hou, Xiaolin; Cui, Defeng; Chen, Wu; Yao, Hua; Xiong, Benhai; Cai, Lirong; Zhang, Hua; Jiang, Linshu
Abstract: Staphylococcus aureus ( S. aureus ) is the major pathogen responsible for mastitis in dairy cows, an important threat to their health, but prevention of S. aureus infection of the mammary gland remains challenging. Berberine hydrochloride (BH), a naturally occurring phytochemical, exhibits a wide range of activities, including antibacterial effects on S. aureus . In this study, we prepared a novel berberine hydrochloride-carboxymethyl chitosan hydrogel (BH-CMCH) with excellent thermosensitivity, injectability and in vitro antibacterial activity. In a rat model of mastitis induced by S. aureus, mammary duct injection of BH-CMCH reduced the bacterial load in infected mammary gland tissue and protected the tissue from damage from infection. In addition, proteomics analysis showed that mammary duct injection of BH-CMCH enhanced autolysosome degradation and promoted the innate immune response by activating the lysosomal pathway and up-regulating related significantly differentially expressed proteins (SDEPs). Taken together, the findings support the potential of BH-CMCH as an antibacterial agent against S. aureus -induced mastitis. Graphical abstract: Unlabelled Image